2015
DOI: 10.1371/journal.pone.0141288
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects and Underlying Molecular Mechanisms of Long-Term Salt Content Diets in Spontaneously Hypertensive Rats

Abstract: Several evidences have shown that salt excess is an important determinant of cardiovascular and renal derangement in hypertension. The present study aimed to investigate the renal effects of chronic high or low salt intake in the context of hypertension and to elucidate the molecular mechanisms underlying such effects. To this end, newly weaned male SHR were fed with diets only differing in NaCl content: normal salt (NS: 0.3%), low salt (LS: 0.03%), and high salt diet (HS: 3%) until 7 months of age. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Additionally, antioxidant treatment with tempol reversed the imbalance of renal RAS components and led to diuresis and natriuresis, lowering obesity-related hypertension. Furthermore, a high salt diet in SHR produced glomerular hypertrophy and decreased ACE2 and nephrin expressions[52]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, antioxidant treatment with tempol reversed the imbalance of renal RAS components and led to diuresis and natriuresis, lowering obesity-related hypertension. Furthermore, a high salt diet in SHR produced glomerular hypertrophy and decreased ACE2 and nephrin expressions[52]. …”
Section: Discussionmentioning
confidence: 99%
“…Rats were placed in individual metabolic cages (Tecniplast 304) during 48 h for analysis of food and water consumption as previous published by Berger et al [21]. The first 24 h were used for adaptation and the following 24 h were used to record food and water intake.…”
Section: Methodsmentioning
confidence: 99%
“…In the kidney specifically, ACE2 is highly expressed in tubular and glomerular epithelium, vascular smooth muscle cells, the endothelium of interlobular arteries, and glomerular mesangial cells [23, 26]. Similar to ACE, expression of ACE2 is altered in many renal disease states such as diabetic nephropathy [27•, 28•], hypertensive renal disease [29•, 30], Alport syndrome [31, 32], and renal fibrosis [33•, 34•]. …”
Section: Ace and Acementioning
confidence: 99%
“…It has generally been understood that the ACE2/Ang(1–7)/Mas axis acts to counterregulate the vasoconstrictive and hypertensive activity of the ACE/Ang II/AT1R axis. Recent studies showed that high-salt diet in spontaneously hypertensive rats decreased ACE2 expression while increasing the ACE/ACE2 ratio, glomerular hypertrophy, loss of the podocytes foot processes, and proteinuria [29•]. These effects were attenuated by low salt and normal salt diets which also decreased the ratio of renal ACE/ACE2 expression [29•].…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation